BAKTERI PELARUT FOSFAT HASIL ISOLASI DARI TIGA LOKASI LAHAN KERING RIZOSFER TANAMAN JAGUNG (Zea mays) DI BANTEN - Firnia, Dewi; ., Nurmayulis; Fatmawaty, Andi Apriany (Jurnal Agroekoteknologi, 2015)
Phosphorus in the soil is essential macronutrient for plant growth. Phosphate solubilizing bacteria are capable of managing phosphate availability in its soluble forms and are often found in the rhizosphere. This study aimed to know the level of total density and characteristics of phosphate solubilizing bacteria isolated from the rhizosphere of maize plants at three dry land locations in Banten. Â The bacteria were isolated using serial plate dilution method. Results showed that four isolated phosphate solubilizing bacteria were obtained. Two isolates were obtained from Curug, one from Walantaka, and one from Petir. The total density of phosphate solubilizing bacterial colonies from those dry land locations were Â 1.9 x 1010 CFU/ml for Curug 1, 1.9 x 1012 CFU/ml for Curug 2, 6x1012 CFU/ml for Walantaka, and 4,8x1010 CFU/ml for Petir.